Incubation and rearing temperature effects on Hsp70 levels and heat stress response in broilers - Givisiez, P. E. N.; Furlan, R. L.; Malheiros, E. B.; Macari, Marcos [UNESP] (Agricultural Inst Canada, 2003)
Incubation temperature (IT) was changed to evaluate if 6-wk-old birds become more tolerant to heat stress. After 13 d of incubation, 470 eggs were submitted to low (36.8degreesC), normal (37.8degreesC) and high (38.8degreesC) temperatures. At day 7 post-hatching, 144 birds were allocated to three rearing temperatures (48 birds/treatment): control/thermoneutral (35-24degreesC), high (33-30degreesC) or low (27-18degreesC) according to the age of the birds. Hsp70 levels in tissues of birds (1 d and 42 d), stress response (42 d) and performance were evaluated. High IT decreased brain (P < 0.01) and liver (P < 0.01) Hsp70 levels, whereas low IT decreased brain (P < 0.01) but increased heart (P < 0.01) Hsp70 levels in 1-d-old chicks. Birds incubated at a low temperature had higher (P < 0.05) feed intake (1-42d). High rearing temperature decreased feed intake (P<0.01) and liveweight (P<0.01). Colonic temperature was lower in birds incubated at a low temperature (P < 0.05) and higher in birds reared in a high temperature (P < 0.05) before heat stress. Birds reared in low temperature had higher increase in colonic temperature after heat stress (P < 0.05). Tissue Hsp70 levels were differently affected by rearing temperature, which affected broiler performance more than IT. Lower IT seemed to increase the sensitivity of birds to heat stress at market age.
Keywords: heat resistance; Hsp70; incubation temperature; rearing temperature